2008
DOI: 10.1021/es801376w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper, Lead, and Cadmium on the Sorption and Desorption of Atrazine onto and from Carbon Nanotubes

Abstract: There are currently few studies on the dual effects of metal ions on the sorption of atrazine and conversely of atrazine on metal adsorption on multiwalled carbon nanotubes (MWCNTs). While a number of sorption models were considered to describe the sorption of atrazine on MWCNTs, the Polanyi-Manes model (PMM) fit the sorption isotherms well with the lowest mean weighted square errors. Atrazine was mainly adsorbed onto the surface and micropores of MWCNTs bundles or aggregates. Hydrogen bonding between azo and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 40 publications
0
96
3
Order By: Relevance
“…This theory would appear to be applicable in this case since MWCNTs form bundles in aqueous media and the spaces between the tubes within the bundles can be regarded as pores. Our data suggest that the PMM should be the recommended model for the adsorption of atrazine by MWCNTs as compared with other nonlinear models, such as Freundlich, Langmuir, dual-Langmuir and dual mode models [23,24].…”
Section: Sorption Isothermsmentioning
confidence: 85%
See 1 more Smart Citation
“…This theory would appear to be applicable in this case since MWCNTs form bundles in aqueous media and the spaces between the tubes within the bundles can be regarded as pores. Our data suggest that the PMM should be the recommended model for the adsorption of atrazine by MWCNTs as compared with other nonlinear models, such as Freundlich, Langmuir, dual-Langmuir and dual mode models [23,24].…”
Section: Sorption Isothermsmentioning
confidence: 85%
“…The adsorption of atrazine on MWCNTs was reported by Yan et al [23] and Chen et al [24]. They found Understanding of adsorption kinetics, thermodynamics and equilibrium is also critical for the design and operation of adsorption equipment.…”
Section: Introductionmentioning
confidence: 93%
“…According to the PMM, pore-filling is an important adsorption mechanism. 24 Irregularly combined aggregates in STI/C 60 could trap more adsorbate into its accessible pores and interstices via rearrangement of particles, and thus result in the adsorption difference with SON/C 60 .…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Previous studies suggested that metal cations may influence the environmental fate of toxic chemicals in soil-water systems [32,33]. Our primary study showed that metallic cations may influence the adsorption of atrazine and 2,4,6-trichlorophenol onto CNTs [28,34], implying that organic chemicals exhibit different environmental behaviors in multiple contaminant system from that in singlesolute systems.…”
Section: Introductionmentioning
confidence: 70%
“…CNTs are considered a superior adsorbent for potential environmental remediation due to their large surface area and high reactivity [16][17][18][19]. The sorption mechanisms of organic chemicals by CNTs include hydrophobic interactions [20][21][22][23], -interaction [24,25], hydrogen bond [26][27][28], electrostatic interactions and Lewis acid-base interaction [26,29]. However, the relative contribution of a given mechanism to the overall sorption is largely unclear, which needs to be further addressed.…”
Section: Introductionmentioning
confidence: 99%